Implementation of Fisher Yates Shuffle Algorithm In Making Learning Animations: Implementation of Fisher Yates Shuffle Algorithm In Making Learning Animations - Saut Dohot Siregar; Dessy Permatasari; Anthony Hutapea; Denis Kinarwan (Jurnal Mantik, 2020)
English is a foreign language that is difficult for most Indonesian children to learn because the pronunciation is different from the language in which it is written. English is an international language used by various countries in the world. This makes it important to introduce English to children from an early age. The basic English that can be learned by children is the introduction of the pronunciation of the alphabet and numbers and general vocabulary in English. One way of learning that can be adjusted according to the level of children's development so that it is interesting and not easily bored is using learning animations. Animated learning is one of the interactive multimedia-based learning media whose use involves interaction with users so that it can increase the involvement of students in the learning process and can improve the results of learning objectives. The implementation of the fisher yates shuffles algorithm is used to randomize the order of the questions in the quiz practice so that the randomized questions will produce different permutations so that users will get unequal question sequences and it is not easy to remember the quiz answers from the given practice questions. The assessment of the feasibility test for this learning animation will be measured using a questionnaire.